The behaviour of aluminum alloy 1050 sheet subjected to impact and perforation process: Experimental and numerical approaches - Bendarma Amine (EDP Sciences, 2021)
The mechanical behavior of aluminum alloy under impact loading using different configurations is described. Perforation tests are referred in this work at wide ranges of specimen using several projectile shapes to analyse their effect on the ballistic curve VR-V0 (conical, hemispherical and blunt), with a diameter of 6.mm. A wide range of impact velocities from 40 to 100 m/s has been used. Experimental and numerical analysis have been carried out to predict the mechanical behaviour of the studied aluminium alloy. This analysis has been done using a high-pressure gas gun. Specimens were prepared from standard 1.0 mm and 1.5 mm thick aluminum sheets with 13x13 cm plates. The resistance and the energy absorbed by the aluminum sheets under dynamic load were obtained by measuring the initial and residual velocities of the projectiles. The experimental and numerical results are presented and compared in terms of ballistic curve VR-V0, a good correlation was observed.